Proposed Methodology For Indonesian State-Owned Enterprises To Conduct Corporate Spin-Off - Adrian Pasca; Dermawan Wibisono; Ima Fatima; Taufik Faturohman; Herry Hudrasyah; Alpha Pudjono (UNIVED Press, 2024)
This research addresses the absence of a formal framework for compliance with corporate spin-offs within Indonesian state-owned enterprises (SOEs). Focusing on a real issue within a state-owned aviation company, the study proposes a comprehensive methodology for SOEs to navigate spin-offs, ensuring adherence to regulatory requirements. By collecting and interpreting relevant regulations and conducting interviews where guidelines are unclear, the research establishes detailed flowcharts outlining the step-by-step procedure. The suggested solution involves following these flowcharts, considering five critical aspects, including government regulation and business law, to successfully implement spin-offs. It is important to note that the proposed methodology is specific to Indonesian state-owned enterprises and is based on government regulations as of November 2023. Users should adapt the methodology in case of regulatory amendments or new compliance-related issues. The research, however, focuses solely on the steps leading to the commencement of new entity operations and does not extend beyond this phase.